Thrombopoietin: From Theory to Reality - Kaushansky, Kenneth (Thrombosis and Haemostasis, 1999)
The term thrombopoietin (TPO) was first penned in 1958 to describe the primary regulator of platelet production. Multiple efforts to purify the hormone were unsuccessful throughout the 1970s and 1980s because the protein was scarce and starting materials for purification biochemically complex. Even purification of thrombocytopenic plasma, which is the richest source of TPO, was unsuccessful.1,2 However, the cloning of the proto-oncogene c-mpl3 opened an alternative route to the identification of TPO. Detailed study of the c-mpl gene revealed that it encoded an orphan hematopoietic cytokine receptor. Its tissue distribution and experiments designed to eliminate its expression suggested that c-mpl encoded the TPO receptor.4,5 In 1994, using three distinct strategies, five separate groups either purified protein or cloned cDNA for TPO.6 This review will focus on the physiology of TPO production and function, concentrating on recent findings that help to explain platelet homeostasis and how our understanding of TPO can translate into better patient care for thrombocytopenic patients.